Unpacking the links between conflict and child welfare: Evidence from a foreign insurgency - Kaila, Heidi; Nawo, Larissa; Son, Hyuk (Households in Conflict Network, 2021)
Violent conflicts have enduring effects on child welfare, but little is understood about the mechanisms underlying these effects. Using data from Cameroon collected from a decade be- fore to shortly after the eruption of the Boko Haram insurgency in the country, we study the immediate impacts of terrorist attacks on child welfare. We find that Boko Haram attacks lead to an immediate decrease in weight-for-height for children under five – an indicator of short- term health and nutrition. Furthermore, we find a reduction in health care service utilization which can prolong and aggravate fever and diarrhea. We do not find effects on dietary diversity. Our results are not driven by changes in the sample of children alive, as child mortality is un- affected by the conflict. The results underscore the importance of health care service provision in conflict-affected areas urgently after the eruption of violence to prevent irreversible impacts from taking place.